Readiness for the Online Classes during COVID-19 Pandemic among Students of Chitwan Medical College - Neupane, Harish Chandra; Sharma, Kalpana; Joshi, Alisha (Journal of Nepal Health Research Council, 2020)
Online learning has been in a rising trend across the world due to increasing technology in education. Corona Virus Disease 2019 (COVID-19) pandemic enforced all the academic institutions to start online classes for the students. But the students’ readiness for the adoption of online learning remains unknown. Hence, this study aimed to assess the readiness of online classes among students. Descriptive cross-sectional web based survey was carried out among 704 students who have enrolled in various streams of Bachelor level programs in Chitwan Medical College. The finding of this study revealed that 87.1% of students from various faculties were ready for online classes during COVID pandemic and 88.8% had internet facility in their home setting. Furthermore, this study found that readiness for online classes was significantly higher among female than male students (89.7% vs.83.5%, p=0.016) and students who had internet accessibility in their residence than those who did not have it (83.8% vs.34.2%, p=<0.001) but there was no significant association between readiness for online classes with academic programs (p=0.062) and years (p=0.905). Therefore, online learning can be considered as a viable alternative method in the academic institutions for the students. Keywords: COVID-19 Pandemic; online classes; readiness; students.